How Have IMF Priorities Evolved? : A Text Mining Approach - Anderson, Gareth; Galang, Paolo; Gamba, Andrea; Medina, Leandro (Washington, D.C. : International Monetary Fund, 2021)
This paper assess how priorities of the IMF's membership have evolved over the past two decades, by using text mining techniques on a unique dataset combining IMFC communiques and constituency statements. Our results reveal significant variation in priorities across time and constituencies. Statements can be characterized by the weight which they place on three key priorities: (i) growth; (ii) debt and development; and (iii) crisis management and quota reform. Sentiment analysis techniques also show that addressing climate change is a topic which is viewed positively by an increasing number of constituencies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Climate; Foreign Exchange; Informal Economy; Natural Disasters and Their Management; Underground Econom